Non-muscle myosin II and the plasticity of 3D cell migration - Cowan, James M.; Duggan, Jacob J.; Hewitt, Breanne R.; Petrie, Ryan J. (Frontiers in Cell and Developmental Biology, 2022)
Confined cells migrating through 3D environments are also constrained by the laws of physics, meaning for every action there must be an equal and opposite reaction for cells to achieve motion. Fascinatingly, there are several distinct molecular mechanisms that cells can use to move, and this is reflected in the diverse ways non-muscle myosin II (NMII) can generate the mechanical forces necessary to sustain 3D cell migration. This review summarizes the unique modes of 3D migration, as well as how NMII activity is regulated and localized within each of these different modes. In addition, we highlight tropomyosins and septins as two protein families that likely have more secrets to reveal about how NMII activity is governed during 3D cell migration. Together, this information suggests that investigating the mechanisms controlling NMII activity will be helpful in understanding how a single cell transitions between distinct modes of 3D migration in response to the physical environment.